Communication Characteristics of Parents of Latino Preschoolers that Predict Improved Readiness to Change for Child Weight After a Clinic Visit. (29th May 2020) - Steen, Emily; Tong, Suhong; Suh, Christina; Glasgow, Russell; Haemer, Matthew
Abstract: Objectives: Communicating effectively about excess weight gain in young children, especially those from low-income and minority families, is a great challenge in primary care settings. This study aims to identify ways clinical communication might be tailored to improve readiness for healthy lifestyle change among Latino parents of preschoolers with: 1. obesity (treatment frame), and 2. high-normal BMI (prevention frame). Methods: A validated measure of readiness to make diet and activity changes for healthy child weight was administered to Latino parents of preschoolers with BMI above the 50th percentile before and after well-child visits at 4 clinics with large Medicaid populations. Parents completed validated measures of acculturation, health literacy, control over health care decision-making, and perceived empathy from medical providers. Parent/child BMI and demographics were collected. Two multivariate linear regression models were created to identify factors associated with increased readiness after either preventive counseling (high-normal child BMI) or treatment counseling (child with obesity). Results: There were 154 parent respondents: mean age 29y [range 22–46y], 95% mothers, 40% Spanish-speaking only, 35% < high school education, 63% income < federal poverty, 47% obese, and 86% reported child weight "not at all a problem" pre-visit. Of 154 children 2–6y, 23% had obesity. Mean baseline readiness was a moderate 17.7 [range 7–34] and increased a mean of + 0.7 [range −13 to + 15] after the visit ( P = 0.01). Model (R 2 = 0.95) for parents of child with obesity: low health literacy β = 4.8 and low control in health decisions β = 6.2 were strongly associated with increased readiness after a visit. In a model (R 2 = 0.20) for parents of child with high-normal BMI: higher health literacy β = 1.5, and low desire for control in health decisions β = 1.99, predicted increased readiness. Conclusions: Parental health literacy and decision-making preferences strongly influence the effectiveness of clinicians' communication about Latino preschoolers' weight. Interventions that help clinicians tailor communication based on these parent characteristics should be studied for their effect on improving readiness to change in parents of Latino preschoolers. Funding Sources: NIH NIDDK.